The interplay of brand trust and image in fostering customer loyalty: a study of Starbucks in Jakarta - Ferdyani, Jovita; Setianingsih, Rita Eka; Dema, Yosef (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
In the high-stakes world of Jakarta's bustling coffee scene, Starbucks faces a relentless challenge: how to navigate the intricate interplay between brand trust, brand image, and customer loyalty. This research dives deep into this dynamic, exploring how these key elements converge to shape consumer loyalty in a market where global forces and local factors collide. Employing a robust quantitative approach, the study uncovers the powerful roles both brand trust and brand image play in driving brand loyalty, with brand image emerging as the dominant force. While trust lays the groundwork by mitigating perceived risks, it is the brand’s image—the emotional connections it fosters, the exclusivity it promises, and the distinct identity it carves—that truly propels loyalty in Jakarta's fiercely competitive market. The findings serve as a wake-up call for Starbucks: to thrive in this ever-evolving landscape, the brand must master the art of managing not only trust but also its image, weaving both elements into a cohesive strategy that strengthens long-term customer loyalty. This research sheds light on how brands can harness the dual power of trust and image to cultivate deep, lasting consumer commitment in emerging markets, driving sustained success in a world where competition is ever- accelerating.